Role of induced magnetic field on transient natural convection flow in a vertical channel: the Riemann sum approximation approach - Jha, Basant K.; Sani, I. (Zielona Góra: Uniwersytet Zielonogórski)
This paper investigates the role of induced magnetic field on a transient natural convection flow of an electrically conducting, incompressible and viscous fluid in a vertical channel formed by two infinite vertical parallel plates. The transient flow formation inside the channel is due to sudden asymmetric heating of channel walls. The time dependent momentum, energy and magnetic induction equations are solved semi-analytically using the Laplace transform technique along with the Riemann-sum approximation method.
Keywords: induced magnetic field; natural convection flow; Riemann-sum approximation